Methodology for improving the assessment of the economic efficiency of transport infrastructure development - D. A. Macheret; A. D. Razuvaev (Управление)
Transport infrastructure, especially railway infrastructure, plays a key role in economic development, ensuring efficient movement of goods and people. It is characterised by high capital intensity, long operational lifespans, and generation of socio-economic effects. Therefore, there is a need to improve the methodology for assessing the economic efficiency of creating and developing transport infrastructure objects. The traditional approach to evaluation is based on discounting cash flows. When applying this method, significant capital investments are compared with devalued effects in subsequent years due to discounting, during which the infrastructure object reaches the specified estimated load. Moreover, it does not consider the fact that the transport infrastructure benefits and holds value not only for the current generation but also for the future one. Additionally, it, as an economic good, cannot be seen as a one-timely consumed product: this transportation service cannot be accumulated. For a more accurate and comprehensive assessment of the efficiency, particularly in the case of railway transport, it is proposed to consider the results of long-term operation of the transport infrastructure at full (estimated) load not in the future but in the present (present сontinious). The economic assessment indicators include initially invested and adjusted capital, annual effect, efficiency ratio, and the value of the transport infrastructure object. The research results aim to provide an adequate assessment of project implementation efficiency in the field in question. In the future, the methodology can be enhanced by defining risks of not ensuring normal infrastructure load throughout the entire calculation period as well as by assessing the reduction in profitability or increase in transportation costs.